Magnetic excitations in non-collinear antiferromagnetic Weyl semimetal Mn3Sn. Issue 1 (December 2018) - Park, Pyeongjae; Oh, Joosung; Uhlířová, Klára; Jackson, Jerome; Deák, András; Szunyogh, László; Lee, Ki; Cho, Hwanbeom; Kim, Ha-Leem; Walker, Helen; Adroja, Devashibhai; Sechovský, Vladimír; et al.
Abstract Mn3 Sn has recently attracted considerable attention as a magnetic Weyl semimetal exhibiting concomitant transport anomalies at room temperature. The topology of the electronic bands, their relation to the magnetic ground state and their nonzero Berry curvature lie at the heart of the problem. The examination of the full magnetic Hamiltonian reveals otherwise hidden aspects of these unusual physical properties. Here, we report the full spin wave spectra of Mn3 Sn measured over a wide momentum—energy range by the inelastic neutron scattering technique. Using a linear spin wave theory, we determine a suitable magnetic Hamiltonian which not only explains the experimental results but also stabilizes the low-temperature helical phase, consistent with our DFT calculations. The effect of this helical ordering on topological band structures is further examined using a tight binding method, which confirms the elimination of Weyl points in the helical phase. Our work provides a rare example of the intimate coupling between the electronic and spin degrees of freedom for a magnetic Weyl semimetal system. Weyl semimetals: magnetic excitations in Mn3 Sn The interplay between the electronic and spin degrees of freedom determines the removal of Weyl points in magnetic semimetal systems. A team led by Je-Geun Park at the Institute for Basic Science and Seoul National University used linear spin wave theory to obtain the full spin wave spectra of antiferromagnetic A-type Mn3 Sn across a broad energy-momentum range. The magnetic Hamiltonian obtained via a local moment model was capable of explaining the experimental inelastic neutron scattering data. Additional density functional theory calculations indicated that the Mn3 Sn low-temperature magnetic structure involves a helical ordering that eliminates the Weyl points, and consequently reduces Mn3 Sn experimental anomalous Hall conductivity. These results indicate how topological Weyl points can be removed by introducing a minor change to the magnetic ground state.